Transforming growth factor-β1 and soluble co-inhibitory immune checkpoints as putative drivers of immune suppression in patients with basal cell carcinoma - Kgokolo, Mahlatse C.M.; Malinga, Nonkululeko Z.; Steel, Helen C.; Meyer, Pieter W.A.; Smit, Teresa; Anderson, Ronald; Rapoport, Bernardo L. (Translational oncology, 2024)
The current study compared the levels and possible associations between systemic soluble immune checkpoints (sICPs, n = 17) and a group of humoral modulators of immune suppressor cells (n = 7) in a cohort of patients with basal cell carcinoma (BCC, n = 40) and a group of healthy control subjects (n = 20). The seven humoral modulators of immunosuppressor cells were represented by the enzymes, arginase 1 and fibroblast activation protein (FAP), the chemokine, RANTES (CCL5) and the cytokines, interleukin-10 and transforming growth factor-β1 (TGF-β1), as well as the M2-type macrophage markers, soluble CD163 (sCD163) and sCD206. The plasma levels of six co-inhibitory sICPs, sCTLA-4, sLAG-3, sPD-1, sPD-L1, sTIM-3 and sPD-L2 were significantly elevated in the cohort of BCC patients (p<0.001-p<0.00001), while that of sBTLA was significantly decreased (p<0.006). Of the co-stimulatory sICPs, sCD27 and sGITR were significantly increased (p<0.0002 and p<0.0538) in the cohort of BCC patients, while the others were essentially comparable with those of the control participants; of the dual active sICPs, sHVEM was significantly elevated (p<0.00001) and TLR2 comparable with the control group. A correlation heat map revealed selective, strong associations of TGF-β1 with seven co-stimulatory (z = 0.618468–0.768131) and four co-inhibitory (z = 0.674040–0.808365) sICPs, as well as with sTLR2 (z = 0.696431). Notwithstanding the association of BCC with selective elevations in the levels of a large group of co-inhibitory sICPs, our novel findings also imply the probable involvement of TGF-β1 in driving immunosuppression in this malignancy, possibly via activation of regulatory T cells. Notably, these abnormalities were present in patients with either newly diagnosed or recurrent disease.